Measuring the impact of the COVID-19 pandemic on elite swimming performance - McFall, T.; Whitehead, J. (Journal of Sports Economics, 2024)
This paper aims to understand how much elite swimmers` training plans for the 2020 Olympics were altered by the COVID-19 pandemic and to measure the effect the interruption had on performances at the United States Olympic Trials Swimming Meet, held in June 2021. To understand better the extent of the disruption caused by the pandemic, we surveyed swimmers and their coaches prior to the meet and found plans were altered in a number of dimensions, including time in the pool, time spent on complementary training activities like weightlifting, and the number of competitions swimmers used to prepare for the Trials. Those surveyed expressed worry that performances would suffer as a result of the disruptions, especially in longer races. We use rankings of United States swimmers from 1999-2019 to measure how much performance suffered from disruptions brought on by the pandemic. We estimate that swimmers` performances generally were worse than forecasted, especially in longer events, and that, somewhat surprisingly, some stroke disciplines performed worse than others. Our findings fit into a larger picture of the societal disruptions to health, education, and labor participation from COVID-19.